ANALYZING THE IMPACT OF STRATEGIC THINKING AND MODELS ON ORGANIZATIONAL PERFORMANCE: AN EXAMINATION OF PORTER’S STRATEGY AND MILLS AND SNOW’S FRAMEWORKS - Aljashaam, Ali Abdulhussein Gaber (PT. Antis International Publisher, 2026)
Objective: Strategic thinking is a key contributor to the future viability and prosperity of organisations, and the research examines the correlation that exists between adopting these strategic models and performance results in organisations such as profitability, market share and growth. Method: Based on mixed-methods research, information was gathered in various industries through surveys, interviews, and evaluation of the strategic documents, where regression and correlation were used to analyse quantitative data delivered, whereas the qualitative data was determined with the help of thematic content analysis and comparative case creates. Result: They show that the organisation with the explicitly stated orientation to a particular strategic model is linked to its better performance as compared to organisations with unclear or inconsistent strategies, and the work shows the mediating role that industry dynamics, managerial perceptions, and internal capabilities play in the effective implementation of the selected strategies. Novelty: The study will contribute to the determination of strategic fit patterns, the definition of the relationship between various strategies and important performance variables, as well as contextual conditions determining strategic effectiveness, with the practical implication that it is better to have a consistent strategic orientation, which is communicated effectively and efficiently to reach the goals of an organisation.